Impact of smoking on early clinical outcomes in patients undergoing coronary artery bypass grafting surgery - Ji, Qiang (J Cardiothorac Surg, 2015)
BACKGROUND: To evaluate the impact of persistent smoking versus smoking cessation over one month prior to surgery on early clinical outcomes in Chinese patients undergoing isolated coronary artery bypass grafting (CABG) surgery in a retrospective study. METHODS: The peri-operative data of consecutive well-documented patients undergoing isolated CABG surgery from January 2007 to December 2013 were investigated and retrospectively analyzed. All included patients were divided into either a non-smoking group or a smoking group according to preoperative smoking records. Furthermore, smokers were divided into either a former smoking subgroup (smokers with smoking cessation over 1 month before surgery) or a current smoking subgroup (persistent smokers). RESULTS: A total of 3730 consecutive patients (3207 male patients and mean 63.6 ± 9.5 years) undergoing isolated CABG surgery were analyzed. Persistent smokers had significantly higher incidence of postoperative pulmonary complications as compared to non-smokers (7.8% vs. 4.5%, p = 0.0002). No significantly differences in both surgical mortality and major postoperative morbidities between smokers with smoking cessation over 1 month before surgery and non-smokers were found. In multiple logistic regression analysis, the risk of postoperative pulmonary complications in persistent smokers was 2.41 times than that in non-smokers, whereas the risk of postoperative pulmonary complications in smokers with smoking cessation over 1 month before surgery was similar to non-smokers. CONCLUSIONS: Persistent smokers had a higher incidence of pulmonary complications following CABG as compared to non-smokers. Smoking cessation more than 1 month before surgery was expected to reduce early major morbidities following CABG surgery.